Peningkatan Kemampuan Pemecahan Masalah Materi Bertoleransi dalam Keberagaman melalui Pembelajaran Berbasis Proyek di Kelas VII.3 SMP Negeri 2 Parungpanjang - Sri Rahayu (Institut Agama Islam Sahid (INAIS) Bogor, 2019)
The purpose of this Classroom Action Research (CAR) is to improve and improve problem-solving skills through project-based learning of the Pancasila and Citizenship Education Subject (PPKn) material Tolerance in Diversity. So far, the Civics learning process emphasizes cognitive aspects more than affective aspects. Civics learning should cover 3 (three) aspects, namely cognitive, affective and psychomotor. The method used is classroom action research through a series of activities starting from the stages of preparing learning designs, implementing learning programs and evaluating learning to the stage of reporting results. The results showed that project-based Civics learning was able to empower students to participate actively in solving problems that occur in the life of society, nation and state. The implementation of project-based learning can improve citizenship problem-solving skills for students in class VII.3 of SMP Negeri 2 Parungpanjang, Bogor Regency, in the 2017/2018 academic year.